2020
DOI: 10.3390/biom10030377
|View full text |Cite
|
Sign up to set email alerts
|

Maytenus disticha Extract and an Isolated β-Dihydroagarofuran Induce Mitochondrial Depolarization and Apoptosis in Human Cancer Cells by Increasing Mitochondrial Reactive Oxygen Species

Abstract: Maytenus disticha (Hook F.), belonging to the Celastraceae family, is an evergreen shrub, native of the central southern mountains of Chile. Previous studies demonstrated that the total extract of M. disticha (MD) has an acetylcholinesterase inhibitory activity along with growth regulatory and insecticidal activities. β-Dihydroagarofurans sesquiterpenes are the most active components in the plant. However, its activity in cancer has not been analyzed yet. Here, we demonstrate that MD has a cytotoxic activity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Based on obtained data showing an increase in ROS generation indicated that RA-ME-induced cytotoxicity and apoptosis in HeLa cells are mediated through ROS generation. The increase level of ROS production has also been reported to be involved in the process of anticancer mechanism of potential anticancer drugs [ 56 ] and plant extract-induced apoptosis in human prostate (CA-2B), human breast (MCF-7), and human lung (PC-9) cancer cells [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Based on obtained data showing an increase in ROS generation indicated that RA-ME-induced cytotoxicity and apoptosis in HeLa cells are mediated through ROS generation. The increase level of ROS production has also been reported to be involved in the process of anticancer mechanism of potential anticancer drugs [ 56 ] and plant extract-induced apoptosis in human prostate (CA-2B), human breast (MCF-7), and human lung (PC-9) cancer cells [ 57 ].…”
Section: Resultsmentioning
confidence: 99%